1993
DOI: 10.1172/jci116330
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a functional receptor for granulocyte colony-stimulating factor on platelets.

Abstract: Since granulocyte colony-stimulating factor (G-CSF) is thought to be a granulocyte lineage-specific cytokine, G-CSF receptors on blood cells other than those of granulocyte or monocyte lineage have not been well investigated. We now report that G-CSF receptors are present on platelets. The expression of G-CSF receptors on platelets was demonstrated by flow cytometry and radioreceptor assay. The mean number of G-CSF-binding sites per cell was 41 and the binding affinity was high (Kd 300 pM), similar to the affi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
72
1
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(77 citation statements)
references
References 25 publications
3
72
1
1
Order By: Relevance
“…IL-lfl and IFN-y enhance the adhesion of thrombin-treated platelets to monocytic leukemia cells, U937, and the release of serotonin by thrombin [25]. G-CSF augments the secondary aggregation of platelets induced by ADP [26]. PDGF inhibited collagen-or thrombin-induced aggregation [27] and secretion of ADP or fl-hexosaminidase in an autocrine manner [28].…”
Section: Discussionmentioning
confidence: 99%
“…IL-lfl and IFN-y enhance the adhesion of thrombin-treated platelets to monocytic leukemia cells, U937, and the release of serotonin by thrombin [25]. G-CSF augments the secondary aggregation of platelets induced by ADP [26]. PDGF inhibited collagen-or thrombin-induced aggregation [27] and secretion of ADP or fl-hexosaminidase in an autocrine manner [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, similar proaggregatory effects are produced by other hematopoietic growth factors, including rHuG-CSF and stem cell factor [45,46]. Studies have been carried out assessing ex vivo aggregatory responsiveness of platelets obtained from animals receiving PEG-rHuMGDF and rHuTPO [30,32,471.…”
Section: Effects Of Mpl Ligands On Platelet Function Ex Vivomentioning
confidence: 99%
“…Shimoda and others have shown that G-CSF receptors are present on the surface of platelets. 2,3 These receptors appear to be functional in vitro 2 and in vivo 4,5 in healthy volunteers. However, the consequences on hemostasis of these findings are conflicting.…”
mentioning
confidence: 99%
“…Other investigators have also observed an increase in platelet aggregation, in platelet activation, in von Willebrand factor and in thrombin-antithrombin complex after G-CSF, but these results could not be confirmed. 2,[4][5][6][7][8][9][10] To date, two cases of thrombosis occurring in normal donors have been reported. 11 The first one was a healthy 54-year-old woman who developed a cerebrovascular accident 2 days after completing an uneventful stem cell donation.…”
mentioning
confidence: 99%